Evaluating the Impact of SGLT-2 Inhibitors on Frailty in Older Adults: A Clinical Review - Al Rashid, Sulthan; Gopalakrishnan, Abinaya Vannapatti; Maideen, Naina Mohamed Pakkir; Almalki, Riyadh S. (Current Drug Safety, 2025)
<span class=
Keywords: sarcopenia